Blended learning in higher education: A bibliometric analysis based on Scopus and WoS data (2015–2024) - Yujie, Long; Nasri, Nurfaradilla Binti Mohamad; Norman, Muhammad Helmi Bin; Shuran, Zhang; Yujie, Long (Edelweiss Applied Science and Technology, 2025)
This study aims to map the intellectual structure, research evolution, and emerging topics of blended learning in higher education. Drawing on bibliometric techniques, the analysis covers 950 publications indexed in Scopus and Web of Science from 2015 to 2024. VOSviewer and CiteSpace were employed to examine publication trends, co-authorship patterns, keyword clusters, journal co-citation networks, and thematic evolution. The findings reveal a notable surge in research output after 2020, driven largely by the COVID-19 pandemic. The United States, China, and Spain emerge as the most productive countries, while journals such as Computers & Education and the British Journal of Educational Technology demonstrate the strongest citation impact. Keyword and cluster analyses highlight five dominant research themes: emergency remote teaching, technology-enhanced learning, course design frameworks, learner attitudes, and technology-driven motivation. The study concludes that blended learning has evolved from model construction to a deeper focus on learner experience and technological integration. Practical implications include the need for stronger international collaboration, more robust theoretical frameworks, and inclusive pedagogical strategies to enhance long-term sustainability in post-pandemic higher education.